Isolation of base stabilized fluoroborylene and its radical cation. Issue 24 (29th May 2019) - Sarkar, Samir Kumar; Siddiqui, Mujahuddin M.; Kundu, Subrata; Ghosh, Munmun; Kretsch, Johannes; Stollberg, Peter; Herbst-Irmer, Regine; Stalke, Dietmar; Stückl, A. Claudia; Schwederski, Brigitte; Kaim, Wolfgang; Ghorai, Sagar; et al.
Abstract : The synthesis and characterization of metal-free fluoroborylene [(Me-cAAC)2 BF] (1 ) is reported. Abstract : Herein, we report the synthesis and characterization of the metal free low valent fluoroborylene [(Me-cAAC)2 BF] (1 ) stabilized by cyclic (alkyl)(amino) carbene (cAAC). The fluoroborylene1 is obtained by the reductive defluorination of Me-cAAC:BF3 with 2.0 equivalents of KC8 in the presence of 1.0 equivalent of Me-cAAC. Due to its highly electron rich nature, 1 underwent one-electron oxidation with 1.0 equivalent of lithium tetrakis(pentafluorophenyl)borate [LiB(C6 F5 )4 ] to form the radical cation [(Me-cAAC)2 BF]˙ + [B(C6 F5 )4 ] − (2 ). DFT studies suggested that the lone pair of electrons is localized on the boron atom in1, which explains its unprecedented reactivity. Both compounds1 and2 were characterized by X-ray crystallography. The radical cation2 was studied by EPR spectroscopy.